Aspleniaceae of Tandikek Mountain West Sumatra - Mildawati, Mildawati; Arbain, Ardinis; Fitrah, Hary (Journal of Tropical Life Science, 2013)
Research on ferns of Aspleniaceae family of Tandikek Mountain in West Sumatra, Indonesia has been done through a survey method and direct collection in the field, followed by a study at Herbarium of ANDA (Andalas University). Eleven species consisting of Asplenium affine, A. batuense, A. belangeri, A. pellucidum, A. phylitidis, A. robustum, A. salignum, A. scalare, A. tenerum, A. unilateralis, and Asplenium sp1. have been found as part of the Asplenium genus. The species of Asplenium genus have been obtained from the elevation of 1231 - 2336 meter above the sea level.Keywords: Aspleniaceae, Tandikek ountain, West Sumatra